(Li, F) co-doped ZnO: Optoelectronic devices applications. (September 2020) - Khuili, M.; Fazouan, N.; El Makarim, H. Abou; Atmani, E.H.; Abbassi, A.; Rai, D.P.
Abstract: One of the challenging tasks of ZnO is to make its p-type doping stable. However, the physical mechanism behind the experimental phenomena of stable ZnO p-type has not been explored so far. Here, the first-principles calculations using the GPW and FP-LPAW methods within Density Functional Theory (DFT) were investigated to explore, on one side, the effect of different substitutional and interstitial sites of Li insertion, and on the other side, the effect of anion-cation co-doping (Li–F) at ratios of 1:1 and 2:1, respectively, on the structural stability as well as electronic, optical, and electrical properties of ZnO. The results showed that Li at the octahedral site (Lioct ) acting as donor-type is more stable than Li at the Zn site (LiZn ) acting as acceptor-type, explaining the difficulty to obtain a stable ZnO p-type conductivity. For equal proportion co-doping under O-rich condition, the formation energy of LiZn –F is lower than that of Lioct -F, indicating that the (LiZn –F) can suppress the effect of Li interstitial and form a completely passive complex. Furthermore, the formation energy of (2LiZn –F) co-doping was more reduced compared to that of (LiZn –F) co-doping with the formation of an occupied shallower acceptor level that improves holes electrical conductivity. Also, a significant absorption in the visible region was shown compared to pure ZnO. Therefore, we can conclude that the presence of the F atom could suppress the formation of interstitial, and (2Li, F) co-doping can be a promising stable p-type of ZnO for use in optoelectronic device applications. Highlights: LiZn doped ZnO allows to have a unstable p-type doped ZnO and a deep acceptor levels. The consequence of this co-doping is the impedance of the occupation of the octahedral sites. 2LiZn –F co-doping showed the existence of shallow acceptance levels. Remarkable absorption and electrical conductivity properties of 2LiZn –F co-doped ZnO. 2LiZn –F co-doping is an alternative to have a stable p-type ZnO.